2015
DOI: 10.1017/s0007114515000148
|View full text |Cite
|
Sign up to set email alerts
|

Fruit and vegetables and cancer risk: a review of southern European studies

Abstract: High intakes of fruit and vegetables may reduce the risk of cancer at several sites. Evidence has been derived mainly from case -control studies. We reviewed the relationship between consumption of vegetables and fruit and the risk of several common cancers in a network of Italian and Swiss case -control studies including over 10 000 cases of fourteen different cancers and about 17 000 controls. Data were suggestive of a protective role of vegetable intake on the risk of several common epithelial cancers. OR f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
161
1
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(175 citation statements)
references
References 94 publications
(92 reference statements)
6
161
1
7
Order By: Relevance
“…Over the last 20 years improvements in screening and treatment modalities have led to decreases in the colorectal cancer death rates. Despite these advances approximately half of patients diagnosed with CRC will eventually die of the disease [1, 2]. Thus, there remains a critical need for more effective preventive and treatment options targeting colorectal cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Over the last 20 years improvements in screening and treatment modalities have led to decreases in the colorectal cancer death rates. Despite these advances approximately half of patients diagnosed with CRC will eventually die of the disease [1, 2]. Thus, there remains a critical need for more effective preventive and treatment options targeting colorectal cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Inadequate diet may also contribute to other RFs, such as arterial hypertension (AH), obesity, and malnutrition. Prospective 18 , case-control 19 , and other types of studies 20 have indicated that consumption of fruits and vegetables is associated with the prevention of cardiovascular diseases, some cancers, and neural tube defects, which has been explained by the content of micronutrients such as potassium, lycopene, folic acid, carotenoids, fibers, polyphenols, water, and low caloric density. Because it is a modifiable factor, it becomes important to adopt public policies that may interfere with behaviors, such as the publication of the Food Guide for the Brazilian Population (2014) 21 and voluntary agreements for the reduction of sodium and trans fats in industrialized foods 22,23 .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies of dietary fiber show benefit but an equal number of studies show no effect in systematic reviews or meta-analyses including thousands or tens of thousands of people [50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66].…”
Section: Fiber In Colorectal Cancer Preventionmentioning
confidence: 99%